Pu-erh tea attenuates obesity by remodeling gut microbiota and activating energy expenditure - Jiang, Xiujuan; Wu, Fan; Xu, Mianhong; Luo, Liyong; Zeng, Liang (Frontiers in Microbiology, 2026)
IntroductionEnergy excess-induced obesity has emerged as a global public health concern, and Pu-erh tea has attracted extensive research interest due to its prominent anti-obesity potential. This study aimed to investigate the anti-obesity activity of Pu-erh tea extract (PTE) and its underlying molecular mechanisms.MethodsHigh-fat diet (HFD)-fed mice were used as the experimental model and subjected to Pu-erh tea extract (PTE) intervention. Whole-body energy metabolism of the mice was monitored using metabolic cages; morphological analysis was performed to characterize the lipid droplet distribution in brown adipose tissue (BAT); transcriptomic and lipidomic techniques were integrated to systematically detect changes in the gene expression profile and lipid composition in BAT; and 16S rRNA gene sequencing was employed to determine alterations in the gut microbiota.ResultsPTE intervention significantly ameliorated HFD-induced obesity in mice without affecting food intake. Metabolic cage monitoring results demonstrated that PTE increased whole-body energy expenditure in mice and shifted the preference of energy substrate utilization toward lipid metabolism. Morphological observation of BAT revealed that lipid droplets in BAT of PTE-treated mice were mainly concentrated in the small-diameter range, which is consistent with the phenotypic characteristic of activated BAT function. Transcriptomic and lipidomic analyses indicated that PTE significantly activated mitochondrial fatty acid β-oxidation and respiratory electron transport in BAT, while markedly reducing the relative contents of lipids such as triglycerides (TG), diglycerides (DG), phosphatidylethanolamine (PE), and phosphatidylcholine (PC). Additionally, 16S rRNA gene sequencing analysis showed that PTE significantly decreased the Firmicutes/Bacteroidetes (F/B) ratio, enhanced the abundance of probiotics, and decreased the abundance of harmful bacteria.ConclusionUnder HFD conditions, the anti-obesity effect of PTE is dependent on the synergistic effect of BAT metabolic remodeling and gut microbiota regulation. PTE activates BAT thermogenic function, promotes fatty acid oxidation, increases gut microbiota richness, and reduces the F/B ratio. These effects collectively enhance systemic energy metabolism and ultimately ameliorate obesity phenotypes. This study provides critical theoretical support for the development of PTE-based anti-obesity functional preparations and lays a foundation for subsequent in-depth exploration of specific molecular targets through which PTE regulates BAT function.